Exploring the Issues of Information and Communication Technology (ICT) Application in Disaster Risk Management: A Case Study of 2014 Major Flood Event in Kelantan - Zakaria, Sharifah Akmam Syed; Azimi, Mohd Azrulfitri; Majid, Taksiah A. (School of Social Sciences, USM, 2017)
Recent study has estimated that 60% of the Malaysian population reside near or along the coastline for their socio-economic. As the threats of natural disaster have grown in terms of intensity and frequency over the years due to climate change, the coastal population of Malaysia are at a higher risk of being affected in so many ways. To successfully mitigate inevitable disaster risks, information and communication systems play significant roles in increasing community preparedness, assisting response and recovery processes and building up capacity for prevention efforts. Athough there has been an established information and communication system designed before to tackle the issues along with standard operating procedures, unfortunately the issues still persist. This paper aims to explore the underlying issues of information and communication technology (ICT) application in disaster risk management based on a real life scenario from the major flood event which hit Kelantan, Malaysia in 2014. Specifically, this study presents evidences using a qualitative analysis for indentifying and classifying ICT application issues related to disaster risk management, prior, during and post disasterhit via a focus group discussion consisting of key stakeholders from the construction industry. The findings show that communication system failure, loss of data and weak coordination inter- and intraagencies are amongst the dominant issues identified by the focus group. It is expected that the insights from this study would constitute formation of a more holistic and effective policies and guidelines to foster ICT applications in disaster risk reduction.